التفسير العلمي في القرآن الكريم بين المؤيدين والمخالفين: دراسة تحليلية نقدية - Usman Usman (Ulumuna, 2014)
One of the patterns of Qur’an interpretation that develops widely in the last and current century is Tafsīr al-'ilmiy. The pattern of Qur’an interpretation has been revealing opinion and argumentation that accept as well as reject it. The article is aimed at analyzing position of this pattern among the Qur’an interpreters, mufassirūn. The method used in this study is comparison analysis. The author concludes that, despite of controversies among the mufassirūn, there is a common intention and objectives they share. They find that Qur’an verses containing scientific signs, known as āyāt kawniyyah, must be considered to bear intrinsically guide to humankind. The mufassirūn are obliged to find and elaborate the guide.